A Comprehensive Financial Decision-Making Literature Review 1964-2021 - Muhammad Asif; Muhammad Khalid, Rashid; Bilal Ahmed, Sheikh; Hafiz, Nazeer Hussain (Allied Business Academies, 2021)
Efficient & Effective Decision Making is a great game that is chalenging from starting of the time to the present time same as the financial decision-making is more complication and tight criteria on current time as per especially uncertainty involved in their decision. The present study is tried to investigate to point out the major Theories and models that play a key role play in financial decision making. Secondary data would be used to achieve the result/conclusion. The authors and their excellence work article that are already published in journals. The golden key statement regarding financial decision-making is to try to share all stakeholders, financial decision-makers and general people.